Digital Transformation in Voluntary Sports Organizations: A Scoping Review on Multi-Level Drivers, Promoting Factors, Forms and Consequences - Pascal Stegmann; Grazia Lang (Current Issues in Sport Science)
Introduction: Digital transformation, as the implementation of information technologies, is increasingly embraced among voluntary sports organizations, including sports federations and clubs (Thompson et al., 2024). These organizations are central pillars of organized sports in Switzerland, playing a critical role in fulfilling the socio-political functions of sports, such as promoting public health, social integration, and civic engagement (Nagel et al., 2020). Despite the increasing adoption of digital technologies, little is known about the drivers, promoting factors, and forms of digital transformation in these organizations (Ehnold et al., 2021; Merten et al., 2022). Furthermore, it remains unclear whether digital transformation helps to effectively address common challenges of voluntary sports organizations, such as recruiting and retaining members and volunteers. Therefore, this review aims to analyse the existing research on digital transformation in voluntary sports organizations to reconcile current approaches in the field of sport management research and identify research gaps.